Proceedings of the 2012 IEEE International Symposium on Antennas and Propagation 2012
DOI: 10.1109/aps.2012.6347999
|View full text |Cite
|
Sign up to set email alerts
|

Radio propagation modeling in indoor stairwell: A K-means clustering approach

Abstract: The propagation characteristics in indoor stairwell differ from those of the conventional indoor signal propagation across different floors and hence, deserve independent scrutiny. In this work, the propagation characteristics in four indoor stairwells have been examined by means of extensive field measurements at two frequency bands -2.4 and 5.8 GHz respectively. It has been found the values of the path loss exponent n for stairwell are higher than those for other indoor environments. More importantly, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The path loss was 35 to 85 dB with link distance ranging from approximately 2 m (with line-of-sight (LOS)) to two floors apart (in non-LOS (NLOS) conditions). In [6][7][8][9], ray tracing simulations and empirical measurements along two types of stairwells in four buildings were conducted at both 2.4 and 5.8 GHz. The transmitter (Tx) was outside the building, and the receiver (Rx) was in the stairwell from the first floor (with LOS) to the third floor (without LOS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The path loss was 35 to 85 dB with link distance ranging from approximately 2 m (with line-of-sight (LOS)) to two floors apart (in non-LOS (NLOS) conditions). In [6][7][8][9], ray tracing simulations and empirical measurements along two types of stairwells in four buildings were conducted at both 2.4 and 5.8 GHz. The transmitter (Tx) was outside the building, and the receiver (Rx) was in the stairwell from the first floor (with LOS) to the third floor (without LOS).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we have found that the polarizations have significant effect in both LOS and NLOS conditions in our measurements where both Tx and Rx are indoors in the stair-wells. No models for floor attenuation factor (FAF) or data on small-scale fading were reported in [6][7][8][9]. We provide a FAF path loss model in this paper, which can be more accurate than traditional log-distance path loss models in multi-floor indoor environments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the propagation characteristics under such an environment are essentially important to the indoor coverage of the 5G communication system. The propagation properties under stair environment have been studied . Basic propagation mechanisms are analyzed by using ray‐tracing method and verified by employing measurements .…”
Section: Introductionmentioning
confidence: 99%
“…Basic propagation mechanisms are analyzed by using ray‐tracing method and verified by employing measurements . More recently, a sectional path loss model of multi‐floor stair was proposed . The path loss model using “walking distance” instead of the separation of the transmitting and receiving antennas was proposed in a recent paper .…”
Section: Introductionmentioning
confidence: 99%
“…In order to satisfy the increasing demands, especially for indoor application, the dense small cell deployment becomes a main direction for the traditional and next-generation communication systems [3,4]. Therefore, site-specific propagation models for different indoor environments with the features of low power and short distance, for example, office rooms [5,6], corridors [7,8], and stairs [9,10], are needed to describe the channel characteristics more accurately. As a basic part of the indoor environments, stair environment plays an important role in our daily life.…”
Section: Introductionmentioning
confidence: 99%